Effect of subcutaneous injections of PYY1-36 and PYY3-36 on appetite, ad libitum energy intake, and plasma free fatty acid concentration in obese males - Sloth, Birgitte; Davidsen, Louise; Holst, Jens Juul; Flint, Anne; Astrup, Arne (American journal of physiology: endocrinology and metabolism, 2007)
1 Department of Human Nutrition, Centre for Advanced Food Studies, Faculty of Life Sciences, University of Copenhagen, Frederiksberg; and 2 Department of Medical Physiology, The Panum Institute, University of Copenhagen, Copenhagen, Denmark Submitted 8 March 2007 ; accepted in final form 1 June 2007 Intraveneous (iv) PYY 3-36 infusions have been reported to reduce energy intake (EI) in humans, whereas few studies exist on effects of PYY 1-36 . The aim of the present study was to examine effects of subcutaneous (sc) injections of PYY 1-36 and PYY 3-36 on appetite, ad libitum EI, plasma concentrations of PYY and free fatty acids (FFA) in obese males. Twenty-four males (BMI 27–40 kg/m 2 ) were randomly assigned to two groups receiving sc injections of either PYY 1-36 or PYY 3-36 in a blinded, placebo-controlled, dose-escalating, cross-over study. Subjects were studied 5 days in succession, with escalating doses of PYY 1-36 [saline, 50, 100, 150, and 200 pmol PYY 1-36 /kg lean body mass (LBM)], or PYY 3-36 (saline, 25, 50, 75, and 100 pmol PYY 3-36 /kg LBM), respectively. PYY injections resulted in dose-dependent increases in plasma PYY levels but no effect on EI in either the PYY 1-36 or the PYY 3-36 group. However, increasing doses of PYY 3-36 , but not PYY 1-36 , resulted in increased ratings of satiety and decreased ratings of hunger, thirst, and prospective food consumption. Although not dose dependently, significant elevation of plasma FFA was seen after injection of PYY 3-36 , but not PYY 1-36 . Although sc administration of PYY was well tolerated, it remains to be determined whether high-dose PYY 3-36 is sufficient in reducing EI in long-term trials, and if so, whether the reduction in EI occurs without nausea. PYY 1-36 is unlikely to be important in regulating energy intake. The PYY 3-36 administrations caused a non-dose-dependent mobilization of FFA, likely through a direct effect. peptide YY; lipolysis; catecholamine; hunger; satiety Address for reprint requests and other correspondence: B. Sloth, Dept. of Human Nutrition, Centre for Advanced Food Studies, Faculty of Life Sciences, Univ. of Copenhagen, 30 Rolighedsvej, DK-1958 Frederiksberg C, Denmark (e-mail: bslatlife.ku.dk )